MODERNISM AND YOUTH IDENTITY IN F. SCOTT FITZGERALD’S THIS SIDE OF PARADISE - Musfirahwaty, Auriza; Sakka, Wahyuni; Harun, Muhammad; Yudith, Madeline (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
The American youth in the twentieth century experienced the era of modernism which the world turn into modern and affected many ascpects of their lives, especially on their youth identity. The research aims at finding out how the modernism affected the American youth identity as reflected in the character’s performance throughout the story. This research employs a qualitative descriptive method with a sociology of literature approach. The data in this research were collected from the descriptions and utterances of the characters and narrator in the novel. The research reveals that the American youth identity in the twentieth century can be observed through their lifestyle, in which the youth already had become accustomed to smoking, drinking and party habits. All these habits continued even after the end of World War I, but there is a difference in the way they do it as the youth faced different situations. The popularity also became an important aspect for the youth at that time. The American values such as individualism and cooperation are also shown in their lives. Individualism value is shown when they believe in themselves and work harder to get what they want, while the cooperation appear through the support from their close relatives when they faced problems. Modernism has brought numerous advantages to humanity through various technological and social developments, but it has also significantly influenced economic life, leading money and business to become central concerns for most of Americans.